Growth and Nitrate Reductase Activity Are Impaired in Rice Osnlp4 Mutants Supplied with Nitrate. (6th March 2021) - Wang, Mengyao; Hasegawa, Takahiro; Beier, Marcel; Hayashi, Makoto; Ohmori, Yoshihiro; Yano, Kenji; Teramoto, Shota; Kamiya, Takehiro; Fujiwara, Toru
Abstract: Nitrate is an important nutrient and signaling molecule in plants, which modulates the expression of many genes and regulates plant growth. In paddy-grown rice ( Oryza sativa ), nitrogen is mostly supplied in the form of ammonium but can also be supplied in the form of nitrate. Several nitrogen transporters and nitrate assimilation enzymes have been identified and functionally characterized in rice. However, little is known regarding the nitrate sensing system in rice, and the regulatory mechanisms of nitrate-related genes remain to be elucidated. In recent years, NIN-like proteins (NLPs) have been described as key transcription factors of nitrogen responses in Arabidopsis thaliana, which implies that OsNLP4 is involved in the regulation of nitrate assimilation and nitrogen use efficiency in rice. Here, we show that OsNLP4 can influence plant growth by affecting nitrate reductase (NR) activity. The growth of OsNLP4 knockdown mutants was reduced when nitrate was supplied, but not when ammonium was supplied. The nitrate concentration was significantly reduced in osnlp4 mutants. Furthermore, the concentrations of iron and molybdenum, essential elements for NR activity, were reduced in OsNLP4 knockdown mutants. We propose that, in addition to the regulation of gene expression within the nitrate signaling pathway, OsNLP4 can affect the NR activity and nitrate-dependent growth of rice. Our results support a working model for the role of OsNLP4 in the nitrate signaling pathway.